O ICMS na prestação do serviço de transporte internacional - Garcia, Cristiano Lemes (2019)
The objective of this study is to analyze the tax obligation arising from the provision of international transport service, when the ICMS taxes - goods movement tax and provision of interstate and inter-municipal transportation services and communications, although operations and services are started abroad, as provided in art. 155, II, which establishes its constitutional legal regime in the 1988 Charter. Special emphasis was given to the hypothesis of ICMS tax on the provision of international transportation services, dealing with doctrinal issues related to constitutional tax jurisdiction, diversity of types of transport, and such as the legal terms and definitions employed in the international scope of transport service provision. The study was carried out from the methodological paradigm of logical-semantic constructivism, in the search for the construction of a meaning for the tax norm under study, both in the semantic and in the syntactic field, from the perspective of: the Constitution of the Federative Republic of Brazil 1988, of the National Tax Code - Law No. 5.172 / 1966, of Constitutional Amendments No. 33/01 and No. 87/15, of Complementary Laws No. 24/75 (article 34, §8, CF / 88) in No. 87/96, as amended, of Senate Resolutions No. 22/1989 and No. 95/1996, State Ordinance Laws, ICMS Regulations, State Decrees and ADIs No. 1.600 and No. 2.669. As a result of this research, the elements of the ICMS tax incidence matrix in the international transportation services are identified, detailing the antecedent and consequent criteria, identifying aspects of the incidence and its peculiarities, such as: delimitation of the rules of competence; the types and modalities of international transport subject to the tax levy rule; the rules of immunity and non-incidence; active and passive subjection; the spatial and temporal criteria; and, finally, the quantitative criterion (basis of calculation and rate)